Effets #xC9;conomiques De La Pand#xE9;mie De Covid-19 Dans La CEMAC (Global Journal of Management and Business Research, 2021)
This paper analyzes the effects of Covid-19 on the economies of the CEMAC countries. In order to do so, our study was based on the estimates and forecasts of the International Monetary Fund (IMF, 2020). This work uses a descriptive approach to describe the effects of the covid 19 pandemic on CEMAC economies. It emerges that the covid-19 pandemic has a negative impact on the economy of the subregion. Four indicators were selected to analyze this negative impact.
Keywords: covid-19; impacts; economic growth; external debt; foreign trade